1999
DOI: 10.1044/jslhr.4204.895
|View full text |Cite
|
Sign up to set email alerts
|

Normative Disfluency Data for Early Childhood Stuttering

Abstract: Although the past 50 years of research on early childhood stuttering and normal disfluency have produced vital information on the general features of disfluent speech behavior of young children, an adequate normative reference for early stuttering does not exist. The purpose of this report is to provide such reference and to provide a basis for clinical needs of differential diagnosis of stuttering from normal disfluency. Data are presented from 90 stuttering children ages 2 to 5 within 6 months of stuttering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
204
6
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(252 citation statements)
references
References 43 publications
29
204
6
13
Order By: Relevance
“…There is also a higher incidence of repetition events in the SG, both of typical disfluencies (up to two repetitions of words) and of atypical disfluencies (more than three repetitions of words, syllables and sounds) as well as atypical disfluencies of block and prolongation types, both in spontaneous speech and in oral reading. Such data confirm those found in the literature (26,27) . Repetitions can be caused by a failure in the temporization of the processes involved in the speech and it is possible that they reflect in the selection of paradigmatic and syntagmatic axes, causing difficulty in the selection of the next term and preventing the linearity of the process (25) .…”
Section: Discussionsupporting
confidence: 83%
“…There is also a higher incidence of repetition events in the SG, both of typical disfluencies (up to two repetitions of words) and of atypical disfluencies (more than three repetitions of words, syllables and sounds) as well as atypical disfluencies of block and prolongation types, both in spontaneous speech and in oral reading. Such data confirm those found in the literature (26,27) . Repetitions can be caused by a failure in the temporization of the processes involved in the speech and it is possible that they reflect in the selection of paradigmatic and syntagmatic axes, causing difficulty in the selection of the next term and preventing the linearity of the process (25) .…”
Section: Discussionsupporting
confidence: 83%
“…Sawyer and Yairi measured stuttering-like disfluencies (SLD) in four consecutive 300-syllable sections of a single 1200-syllable speech sample for each child. SLD were those disfluencies more typical of stuttered speech, including part-word repetitions, single-syllable whole word repetitions, and disrhythmic phonation (blocks, prolongations, and broken words; Ambrose & Yairi, 1999). Results indicated that, in general, group means for SLD grew larger as the sample size increased, and specifically, there were significantly more SLD per 100 syllables in the fourth 300-syllable section than in the first.…”
Section: Introductionmentioning
confidence: 73%
“…Severity was assessed using a weighted measure that reflected the frequency and type of SLD as well as the extent or length of the disfluencies (Ambrose & Yairi, 1999). One advantage of the weighted scale is that it accounts for the considerable contribution of disrhythmic phonation and a large number of repetition units that contribute to the perception of severity (Costello & Ingham, 1984;Zebrowski & Conture, 1989).…”
Section: Participantsmentioning
confidence: 99%
“…Yairi (1997) also recommends use of this principle, despite the ''nonstuttering'' diagnosis applied to the child described above as Participant 15. Ambrose and Yairi (1999) extended the principle by emphasizing the proportions of SLDs in relation to other disfluencies when attempting to diagnose stuttering in children (see below).…”
Section: Methods Of Measuring Stutteringmentioning
confidence: 99%